Early Ripening and Marketability of the Products in Different Types of the Sweet Cherry Orchards in the Ukrainian Forest-Steppe - Kishchak, Olena; Kishchak, Yuriy; Slobodianiuk, Andriy (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2023)
The considerable vigour of the sweet cherry (Prunus avium L.) trees‘ growth and their late fruit-bearing beginning complicate the industrial highly efficient orchard creation. Besides, the requirements of the global trade networks increased to the fruit marketable quality as well. Therefore, the purpose of our research was the selection of large-fruited cultivars bred in Ukraine as well as clonal rootstocks including Gisela 5, Gisela 6, and Studenykivska as well as cvs Krupnoplidna, Etyka, and Annushka appeared to influence positively the beginning of the orchard’s fruit-bearing, the acceleration of the early maturity, providing the constant high fruits productivity and marketable quality. The field, laboratory, and comparative methods of the investigations were applied as well as the statistical ones. The highest productivity was ensured by the semi-vigorous rootstocks (like Gisela 6). Their average yield per tree in the five-year age was 14.4–18.5 kg.tree-1 depending on the variety. The maximum number of trees loaded with fruits was provided by Krupnoplidna (28.9 kg.tree-1). On account of the surface unit was 25.7 t.ha-1. It was noted that irrespective of this index the trees at a young age were able to ensure the highest fruits marketable quality. The highest qualitative indices were provided in the orchards where the cultivar of the middle and middle-late ripening terms was used in which products unidimensional job lots were formed (74.8–100%) with the fruit diameter 29.8–35 mm. At the same time, more rapid rates of fruits diminution were noted in the orchards on the semi-dwarfing rootstocks ’Gisela 5‘ and ’Studenykivska‘ where the average fruit mass in the eight-year age reduced almost by two times as compared to those which were formed in the 5–6 year orchards. Therefore, it is most expedient to create cherry plantations on semi-vigorous rootstock Gisela 6, which provides 1.8–2.1 times higher productivity of trees, as well as the high marketable quality of fruits during the period of productive use of plantations.